Morphological distinction of species of Thrichomys (Rodentia: Echimyidae) through ontogeny of cranial and dental characters - Da S. A. Neves, Antonio Carlos; Pessôa, Leila Maria (Zootaxa, 2011)
Recent cytogenetic and molecular studies changed the monotypic status of the genus Thrichomys, recognizing at least four species. In this study we analyzed cranial and dental characters throughout ontogeny to investigate morphological differences between three species from Brazil: Thrichomys laurentius, from Caruaru, Pernambuco State; Thrichomys inermis, from Morro do Chapéu, Bahia state; and Thrichomys pachyurus, from Barão de Melgaço, Mato Grosso state. The samples were chosen by proximity to type localities and availability in collections. We described age classes for each species, grouped in four categories: juvenile, sub-adult, adult and senile. The unique pattern of wear of cheekteeth described in literature to the genus was made for a population from Bodocó, Pernambuco and was different of the patterns described in this study. The three patterns of tooth wear also differed from each other. In the analysis of the skull, three of the 14 characters observed did not vary during the ontogeny of each species or among the species examined. Four characters observed varied during the ontogeny of the three species examined, but in a similar way. The eight other cranial characters analyzed varied during ontogeny of the species and differently in each species. Among these eight characters, four were useful to distinction of species of Thrichomys. These characters were stable during the ontogeny of each species but were different among the three species: the shape of the interpremaxilar foramen, the shape of the incisive foramen, the shape of hamular processes, and the shape of the angle of mesopterygoid fossa. The description of the ontogenetic series of these species showed marked differences between them, corroborating morphologically the distinction of three different species.